Accidental Laser-Induced Macular Holes: A Case Series. (July 2019) - Alnuaimi, Rawdha; Issa, Sharif
Purpose: The purpose of this article is to report various types of maculopathy caused by momentary exposure to a high-power handheld blue laser. Methods: The design included a consecutive case series of 4 patients. Evaluation included a full ophthalmic examination and macular spectral-domain optical coherence tomography. Main outcome measures included an analysis of the types of maculopathy and vitreoretinal pathological features. Results: All patients were young men. The most common setting for injury was accidental at play. The types of maculopathies encountered were a full-thickness macular hole (FTMH) in 4 eyes, a premacular subhyaloid hemorrhage in 5 eyes, premacular sub–internal limiting membrane hemorrhage in 2 eyes, an outer retinal disruption at the fovea in 1 eye, an epimacular membrane in 1 eye, and a schisis-like cavity in 1 eye. Snellen best-corrected visual acuity (BCVA) at presentation ranged from 20/40 to 4/200 (mean, 20/290). Only 4 eyes (29%) improved spontaneously with increase in vision, whereas 10 eyes (71%) required intervention. All 4 FTMHs were closed successfully after pars plana vitrectomy. Final mean BCVA in all cases was 20/35. Conclusions: Exposure to high-power handheld laser devices can cause a variety of maculopathies that can reduce central vision permanently. Although vision may improve spontaneously, most cases require intervention. Unrestricted access to commercially available high-power handheld laser devices is dangerous, and public awareness should be encouraged.